Problem 22
Answer: x = 3/5
---------------------------------------
Step-by-step explanation:
y = kx is the general form for direct variation. K is some constant.
Plug in (x,y) = (-3,5) to find k
y = kx
5 = k*(-3)
-5/3 = k
k = -5/3
-------------
The equation is y = (-5/3)x. Now plug in y = -1 to find x
y = (-5/3)x
-1 = (-5/3)x
(-5/3)x = -1
x = -1*(-3/5)
x = 3/5
==========================================================
Problem 23
Answer: y = 21
---------------------------------------
Step-by-step explanation:
Same idea as above. First we need to find k.
y = kx
-7 = k(-3) .... plug in x = -3 and y = -7
-3k = -7
k = 7/3
The equation is y = (7/3)x
-------------
We can use this to find y when x = 9
y = (7/3)x
y = (7/3)*9 .... plug in x = 9
y = 21
==========================================================
Problem 24
Answer: y = 10
---------------------------------------
Step-by-step explanation:
First find k
y = kx
25 = k*15
25/15 = k
5/3 = k
k = 5/3
The equation is y = (5/3)x
------------
Now find y when x = 6
y = (5/3)x
y = (5/3)*6
y = 10